TINGKAT KEBISINGAN DI KAMPUS MIPA SELATAN UGM NOISE LEVEL ON SOUTHERN CAMPUS OF MIPA UGM - , FITRIA, Dr.Bambang Murdaka Eka Jati, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of the most annoying environmental impact is noise and the main noise source is traffic. The research aim to know whether a viable campus south of MIPA UGM is used as a place of learning that is condisive or not. The equipment used in the study is Sound Level Meter (SLM), SLM is used in the study to measure noise level. The region location is used noise level devided by four location, there are location A, B, C, and D. Each location is used noise level data appropriate times has determined. According to KEPMENAKER No.Kep-51 MEN/1999 the zone which is recomendated for education place is Zone B 45-55dB. Data result on campus south of MIPA UGM almost noise level more intensity which recomendated. From here can conclude that the building campus south of MIPA UGM include as a place of learning not condusive because the atmosphere of campus is noise. The recommendated technique to lower the noise level is method around building campus which appear traffic is made embankment from a heap of soil or material until to can lower noise source from traffic.